Study of pre-equilibrium emission of light complex particles from Fe and Bi induced by intermediate energy neutrons - R. Bevilacqua (2018)
We have measured double differential cross sections (DDX) for emission of hydrogen- and helium-isotopes in the interaction of 175 MeV quasi-monoenergetic neutrons with Fe and Bi using the Medley setup at the The Svedberg Laboratory (Uppsala, Sweden). We compared experimental DDX with calculations with the TALYS code, which includes exciton model and Kalbach systematics; the code fails to reproduce the emission of complex light ions, generally overestimating it. We propose an correction for the application of the Kalbach phenomenological model in the TALYS code by introducing a new energy dependence for the nucleon transfer mechanism in the pre-equilibrium emission region. Our results suggest also evidence for multiple pre-equilibrium emission of composite particles at 175 MeV.